PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS QUIZLET PADA MATERI FPB DAN KPK KEPADA SISWA SDN 1 GUNUNG SARI - Gede Agus Ary Partawan; I Komang Sesara Ariyana; I Komang Wahyu Wiguna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to develop flashcard- and Quizlet-based learning media for mathematics instruction, specifically on the topics of Greatest Common Divisor (GCD) and Least Common Multiple (LCM), for sixth-grade students at Gunung Sari Elementary School No. 1, as well as to assess the validity and practicality of the developed media. This study used the D&D (Design & Development) model, which consists of the Analyze, Design, Development, and Evaluation stages. The research subjects involved instrument experts, media experts, subject matter experts, language experts, sixth-grade teachers, and sixth-grade students, selected through one-on-one interviews with three participants and small-group discussions with 12 participants. Data collection techniques included observation, interviews, documentation, and questionnaires. Data analysis employed both descriptive and qualitative methods (mixed methods). The research results show that (1) in the design phase, the researcher developed the media based on the results of the observations conducted, thereby producing higher-quality media that were subsequently revised by the experts to further improve them; these revised media influenced the results of the subsequent validity and practicality tests, (2) Regarding validity, the researchers obtained highly satisfactory and high results, with Aiken’s V scores of 0.90 from the subject matter expert, 0.97 from the media expert, and 0.90 from the language expert; and (3) regarding practicality, the results of the practicality test showed a 94.7% rating from students, categorized as “very practical.”